BEEKEEPING SUPPORT IN THE EUROPEAN UNION COUNTRIES - Janusz MAJEWSKI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The analysis and support structure of the beekeeping sector in the European Union countries was analyzed. The level of support for this sector of agriculture in the years to come increased and in the years 2017-2019 is 72 million EUR per year. The amount of support beekeeping depends mainly on the number of hives. The average value of support for bee colony in most countries ranges from 4.35 to 4.63 EUR per year. The amount of support expressed as the equivalent of beekeeping honey indicating little relevance of this action, since the value of the support is equal to the EU average of 0.65 kg multiflorous honey, that varies from 0.3 to 1.33 kg